(untitled) (Baghdad Science Journal, 2025)
A series of Schiff bases linked to phthalimidyl phenyl sulfonate moiety have been synthesized via multistep synthesis. The first step involved reaction of phthalic anhydride with aniline producing N-phenyl phthalamic acid which was subsequently dehydrated to the corresponding N-phenyl phthalimide via treatment with acetic anhydride and anhydrous sodium acetate. The synthesized imide was treated with chlorosulfonic acid in the third step producing 4-(N-phthalimidyl) phenyl sulfonyl chloride which was introduced in reaction with 4-hydroxy acetophenone in the fourth step producing 4-[4-(N-phthalimidyl) phenyl sulfonate] acetophenone and this in turn was introduced successfully in condensation reaction with various aromatic primary amines affording the desired new Schiff bases. The newly synthesized compounds were characterized through spectral data including FTIR, 1HNMR and 13CNMR. Antimicrobial activity of the prepared Schiff bases was evaluated against two types of bacteria and one type of fungi and the new Schiff bases were found to exhibit good antimicrobial activity against the tested organisms.